Predictors of successful fitting of vaginal pessary for female pelvic organ prolapse - Farah Wali Lone; Joanne Palmer (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2019)
Introduction and Hypothesis: There is variable evidence on predictors of successful fitting of vaginal pessary for female pelvic organ prolapse (POP). This study evaluates measures that may predict successful pessary fitting for POP. We hypothesized that previous hysterectomy and higher body mass index (BMI) do not affect the ability to retain a pessary and that POPQ measures cannot predict a successful pessary fitting. Methods: This is a retrospective observational study of women with POP referred to the urogynaecology clinic between October 2012 and Oct 2015, who agreed to have pessary insertion. The option of vaginal pessary is routinely offered to these women. Patient demographics, pelvic organ prolapse quantification (POPQ), size and type of pessary use and its outcome were recorded. Results: Of the 259 women who opted to use a pessary, 201(78%) successfully retained the pessary at 4 weeks after insertion. Various pessary types were used. Predictors of successful pessary fitting were larger total vaginal length, shorter genital hiatus, shorter genital hiatus/total vaginal length ratio, larger perineal body length and early stage anterior vaginal wall prolapse predicted successful pessary fitting. Hysterectomy status did not predict fitting (p>0.05). Most of the patient variables did not predict the success or failure of pessary fitting except for the BMI. Women with a higher BMI increased the odds of a successful pessary fitting (OR 1.09). Conclusion: Most women with POP can be successfully fitted with a vaginal pessary. POPQ measures can be helpful in determining successful pessary fitting Brief Summary: Successful vaginal pessary fitting can be achieved for most women with POP. POPQ measures can help in determining successful fitting of a vaginal pessary.